THE STUDENTS’ ENGLISH SPEAKING COMPETENCE BASED ON KTSP CURRICULUM - Acep Haryudin (Eltin Journal : Journal of English Language Teaching in Indonesia, 2016)
The primary aim of this research is to investigate and measure level of students’competency based on KTSP Curriculumin English Speaking Skill at second gradestudengts of SMAN 1 Cilograng-Banten. In this research, the writer used quantitativemethod.The result of data analysis indicate that the scores and students’ competencelevels of English speaking skills are; pronunciation 3,38 (average level competence),grammar 3,61 (high level competence), vocabulary 3,23 (middle level competence),fluency 3,42 (middle level competence),and comprehension 3,47 (middle level competence). The writer calculated and concluded whole data and the cumulative data is 3,49. If the Mean score is identified in the qualitative scale, the result is in thedistance of 3,5-4,5 (60%) It means that level of students’ competence in EnglishSpeaking skill is in intermediate level.Keywords:Students’ Competence, KTSP Curriculum, and Speaking Skill